DIVING FOR PEARLS. - THOMSON, KATHERINE (CURRENCY Press, 2017)
Katherine Thomson's story about aspiration and reinvention is one of the great Australian plays. Set in Wollongong during the economic rationalism of the late 80s, Diving for Pearls remains startlingly relevant--the political decisions of that time planted the seeds of divide we continue to witness between those with opportunity, and those without.